2011
DOI: 10.1002/fam.1123
|View full text |Cite
|
Sign up to set email alerts
|

The new and improved NIST Dragon's LAIR (Lofting and Ignition Research) facility

Abstract: SUMMARY Several studies suggest that the firebrands are a major cause of structural ignition of Wildland–Urban Interface fires in USA and Australia. For 40 years, past firebrand studies have focused on how far firebrands fly and do not assess the vulnerabilities of structures to ignition from firebrand showers. The development of the National Institute of Standards and Technology (NIST) Dragon has allowed the quantification of structure ignition vulnerabilities of full‐scale building assemblies. Full‐scale tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…When comparing the mass required for Cedar crevice ignition of Manzello and Suzuki [42], to the deck results reported here, it was observed that the decking assemblies required significantly more mass of firebrands to produce flaming ignition. This was expected since the firebrands were not allowed to accumulate in such a tight, V-shaped crevice as the bench-scale experiments, resulting in larger heat losses (see Equation 1).…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…When comparing the mass required for Cedar crevice ignition of Manzello and Suzuki [42], to the deck results reported here, it was observed that the decking assemblies required significantly more mass of firebrands to produce flaming ignition. This was expected since the firebrands were not allowed to accumulate in such a tight, V-shaped crevice as the bench-scale experiments, resulting in larger heat losses (see Equation 1).…”
Section: Resultsmentioning
confidence: 55%
“…The net heat flux, q" net to the fuel bed from the accumulated firebrands is given as (see Figure 7): where q" FB is the heat flux from the firebrands, q" conv is the convective heat flux, q" rad is the radiative heat flux, " m  is the mass loss rate per unit area, and L v is the heat of gasification of cedar. The ignition time for thermally thick materials is known to be proportional to the room-temperature density, ρ, of the material and inversely proportional to the square of the net heat flux to the fuel bed, q" net [41][42] Therefore, for wood with similar moisture content, and the same net heat flux, the wood with the highest density is expected to take the longest time to ignite. The densities were measured for the three wood types, and the Douglas-Fir boards (534 kg/m 3 ) were found to have the largest density, followed by Redwood boards (437 kg/m 3 ), and then Cedar boards (361 kg/m 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, full-scale experiments are required to observe vulnerabilities of structural components to wind-driven firebrand showers and, yet bench scale test methods afford the capability to evaluate firebrand resistant technologies such as firebrand resistant sarking. The bench scale Dragon's LAIR (Lofting and Ignition Research) facility, described in detail elsewhere [13], is a unique experimental platform to evaluate sarking material performance to wind-driven firebrand showers. Once promising technologies are identified, full scale tests, similar to those described in this paper, could be conducted to test the performance to provide firebrand resistant tile roofing assemblies.…”
Section: Discussionmentioning
confidence: 99%